ANALISIS KESALAHAN SISWA DALAM MENYELESAIAKAN SOAL CERITA TENTANG PERBANDINGAN - Supriyanto (PREMIERE : Journal of Islamic Elementary Education, 2019)
This study aims to describe the location, type, and factors causing students to make mistakes in solving the story of the comparison. And to arrange alternative learning so that errors do not happen again. The determination of research subjects based on the results of the analysis of student work outcomes on the question of diagnostic tests provided. With diagnostic tests can be known location and type of student error, while to determine the factors causing the error obtained from an interviews with the subject of research. From the research, it is known that the research subjects made mistake in every step of problem-solving that is: understanding the problem, devising a plan, carrying out the plan, and looking back and make a conclusion. The types of mistakes made by the students are as follows: 1) the error of facts: incomplete in writing what is known about, 2) misconceptions: not making the right plan, wrong in determining the percentage of a value, wrong in comparing, Determining the values ​​compared, wrong in determining the type of comparison, 3) principle error: incorrect in using formulas to determine percentages, and incorrect in determining unknown values ​​in comparison, and 4) operation errors: errors in simplifying fractions. Factors that cause errors are a lack of thorough students in reading and understanding problems, difficulties in using and analyzing information on the problem, the existence of a misconception about the comparison. Based on the characteristics of factors causing mistakes made by students, then Problem Based Learning is one effective way to embed the concept of comparison and familiarize students in solving math problems.